Tracking Effects of Problematic Social Networking on Adolescent Psychopathology: The Mediating Role of Sleep Disruptions - Vernon, Lynette; Modecki, K.; Barber, B. (Lawrence Erlbaum Associates, Inc., 2017)
Copyright © 2017 Society of Clinical Child & Adolescent Psychology. Concerns are growing about adolescents’ problematic social networking and possible links to depressed mood and externalizing behavior. Yet there remains little understanding of underlying processes that may account for these associations, including the mediating role of sleep disruption. This study tests this putative mediating process and examines change in problematic social networking investment and disrupted sleep, in relation to change in depressed mood and externalizing behavior. A sample of 874 students (41% male; 57.2% Caucasian; baseline M age = 14.4 years) from 27 high schools were surveyed. Participants’ problematic social networking, sleep disruption, and psychopathology (depressed mood, externalizing behaviors) were measured annually over 3 years. Longitudinal mediation was tested using latent trajectories of problematic social networking use, sleep disruption, and psychopathology. Both problematic social networking and sleep disruption underwent positive linear growth over time. Adolescents who increasingly invested in social networking reported increased depressed mood, with around 53% of this association explained by the indirect effect of increased sleep disruptions. Further, adolescents who increasingly invested in social networking also reported increased externalizing behavior; some of this relation was explained (13%) via increased sleep disruptions. However an alternative model in which increased externalizing was associated with increased social networking, mediated by sleep disruptions, indicated a reciprocal relation of similar magnitude. It is important for parents, teachers, and psychologists to minimize the negative effects of social networking on adolescents’ psychopathology. Interventions should potentially target promoting healthy sleep habits through reductions in social networking investment and rescheduling usage away from bedtime.